Wiener Index Calculation on the Benzenoid System: A Review Article - Dwindi Agryanti Johar; Asep Kuswandi Supriatna; Ema Carnia (Department of Matematics, Universitas Padjadjaran, 2023)
The Weiner index is considered one of the basic descriptors of fixed interconnection networks because it provides the average distance between any two nodes of the network. Many methods have been used by researchers to calculate the value of the Wiener index. starting from the brute force method to the invention of an algorithm to calculate the Wiener index without calculating the distance matrix. The application of the Wiener index is found in the molecular structure of organic compounds, especially the benzenoid system. The value of the Wiener index of a molecule is closely related to its physical and chemical properties. This paper will show a comprehensive bibliometric survey of peer-reviewed articles referring to the Wiener index of benzenoid. The Wiener index values of several benzenoid compounds using cubic polynomial are also reported. The Wiener index of benzenoid supports much of the research and provides productive citations for citing the study. Keywords: Wiener index, benzenoid, distance matrix, chemical properties, cubic polynomial, topological.